2010
DOI: 10.1177/1077801210382866
|View full text |Cite
|
Sign up to set email alerts
|

Aggression and Sexual Behavior in Best-Selling Pornography Videos: A Content Analysis Update

Abstract: This current study analyzes the content of popular pornographic videos, with the objectives of updating depictions of aggression, degradation, and sexual practices and comparing the study's results to previous content analysis studies. Findings indicate high levels of aggression in pornography in both verbal and physical forms. Of the 304 scenes analyzed, 88.2% contained physical aggression, principally spanking, gagging, and slapping, while 48.7% of scenes contained verbal aggression, primarily name-calling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
362
1
23

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 408 publications
(417 citation statements)
references
References 29 publications
10
362
1
23
Order By: Relevance
“…Sexual skills to sexually arouse and satisfy a partner, such as touching genitals or giving oral sex, are also frequently portrayed in SEIM (Gorman et al, 2010;Klaassen & Peter, 2015;Van Doorn, 2010). For instance, characters compliment sexual partners for their sexual performances (Bridges, Wosnitzer, Scharrer, Sun & Liberman, 2010) and explicitly show the enjoyment caused by a partner's sexual skills (Gorman et al, 2010). Moreover, more than 90% of the characters involved in sexual interactions in SEIM appear to be SEIM, PERFORMANCE ORIENTATION, ENJOYMENT, UTILITY 6 sexually experienced and in control of the sexual actions that they perform (Vannier, Currie, & O'Sullivan, 2014).The characters' sexual proficiency is sometimes expressed in propositions (e.g., ''I'll teach you something'') in the dialogues between characters and/or the title or description of SEIM (Vannier et al, 2014, p.257).…”
Section: Exposure To Seim and Adolescents' Sexual Performance Orientamentioning
confidence: 99%
“…Sexual skills to sexually arouse and satisfy a partner, such as touching genitals or giving oral sex, are also frequently portrayed in SEIM (Gorman et al, 2010;Klaassen & Peter, 2015;Van Doorn, 2010). For instance, characters compliment sexual partners for their sexual performances (Bridges, Wosnitzer, Scharrer, Sun & Liberman, 2010) and explicitly show the enjoyment caused by a partner's sexual skills (Gorman et al, 2010). Moreover, more than 90% of the characters involved in sexual interactions in SEIM appear to be SEIM, PERFORMANCE ORIENTATION, ENJOYMENT, UTILITY 6 sexually experienced and in control of the sexual actions that they perform (Vannier, Currie, & O'Sullivan, 2014).The characters' sexual proficiency is sometimes expressed in propositions (e.g., ''I'll teach you something'') in the dialogues between characters and/or the title or description of SEIM (Vannier et al, 2014, p.257).…”
Section: Exposure To Seim and Adolescents' Sexual Performance Orientamentioning
confidence: 99%
“…Finally, due to changes in the pornography industry, readily available pornography is increasingly degrading to and violent toward women (Bridges 2010;Bridges, Wosnitzer, Scharrer, Sun, andLiberman 2010 Jensen 2010). Indeed, violence and degradation are hallmarks in the industry of "good" pornography (Tyler 2010).…”
Section: Introductionmentioning
confidence: 99%
“…According to the United Nations Statistical Commission, domestic, sexual and psychological violence offences against females are evident in Egypt [20] , and such acts are depressingly rising [21] . A previous report by the International Communication Association (2007) concluded that 30% of all internet traffic contains porn content, 88.2% of porn scenes include aggressive acts, and 94% of these acts are directed toward women [22] . Compared with males, female activists and bloggers receive sexrelated attacks particularly in male-dominated spaces [23] .…”
Section: ** Significant At P<0001mentioning
confidence: 99%